2018
DOI: 10.3892/etm.2018.7050
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the relationship between Oxford classification,IgM deposition and multiple indexes and the adverseprognosis of patients with primary IgA nephropathy and related risk factors

Abstract: The risk and influencing factors of prognosis in patients with primary IgA nephropathy (IgAN) were explored. One hundred and twenty-four patients who were diagnosed with IgA nephropathy in West China Hospital of Sichuan University were selected as the study subjects. The baseline data were recorded. All patients were followed up for 3 years. Patients with poor prognosis were defined as poor prognosis group, and the patient with no adverse prognosis was defined as a good prognosis group during the follow-up per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…We found by Cox regression that interstitial brosis and IgA deposition strength were the independent risk factors for IgAVN, and interstitial brosis was a risk factor for IgAN. Interstitial brosis is a signi cant factor in uencing kidney outcomes under the comprehensive comparison [30][31][32][33]. In addition, our study discovered that cellular crescents in IgAVN were more common in glomerular lesions, suggesting an acute course of kidney lesions in IgAVN.…”
Section: Discussionmentioning
confidence: 62%
“…We found by Cox regression that interstitial brosis and IgA deposition strength were the independent risk factors for IgAVN, and interstitial brosis was a risk factor for IgAN. Interstitial brosis is a signi cant factor in uencing kidney outcomes under the comprehensive comparison [30][31][32][33]. In addition, our study discovered that cellular crescents in IgAVN were more common in glomerular lesions, suggesting an acute course of kidney lesions in IgAVN.…”
Section: Discussionmentioning
confidence: 62%
“…Various studies have indicated various prognostic parameters of IgAN. For example, proteinuria, serum creatinine, and Oxford classification indices were considered risk factors for the early diagnosis of IgAN [ 19 ]. Moreover, some other new indicators also have excellent prognostic predictive ability in IgAN patients, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Because GNRI can reflect the status of nutrition and inflammation, this may impact the synthesis of hemoglobin. Serum creatinine, eGFR, proteinuria and the Oxford classification are generally used for the diagnosis and classification of IgAN ( Hao et al, 2019 ). This study did not find that the GNRI scores were related to serum creatinine and eGFR as calculated, but they were related to histological lesions.…”
Section: Discussionmentioning
confidence: 99%